2019
DOI: 10.3389/fphys.2019.00294
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte as Spatiotemporal Integrating Detector of Neuronal Activity

Abstract: The functional role of astrocyte calcium signaling in brain information processing was intensely debated in recent decades. This interest was motivated by high resolution imaging techniques showing highly developed structure of distal astrocyte processes. Another point was the evidence of bi-directional astrocytic regulation of neuronal activity. To analyze the effects of interplay of calcium signals in processes and in soma mediating correlations between local signals and the cell-level response of the astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 57 publications
1
58
0
1
Order By: Relevance
“…The model provides a basis for possible modifications in order to apply integrated information concepts to systems exhibiting similar, but more complicated behavior (in particular, to neuronal [ 26 , 27 , 28 , 29 ] and neuron–astrocyte [ 24 , 30 ] networks). Such modifications might incorporate non-trivial spatial patterns in bursting, and causal interactions within and between the spiking and bursting subsystems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model provides a basis for possible modifications in order to apply integrated information concepts to systems exhibiting similar, but more complicated behavior (in particular, to neuronal [ 26 , 27 , 28 , 29 ] and neuron–astrocyte [ 24 , 30 ] networks). Such modifications might incorporate non-trivial spatial patterns in bursting, and causal interactions within and between the spiking and bursting subsystems.…”
Section: Resultsmentioning
confidence: 99%
“…The mentioned conditions were derived under the assumption of absent correlation between spontaneous activity in individual bits (24). If correlation exists and is positive, then s 1 > s A s B , or s B < s 1 /s A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that astrocyte can act as temporal and spatial integrator, hence, detecting the level of spatio-temporal coherence in the activity of accompanying neuronal network. Currently actively discussed hypothesis is that the astrocytic calcium activity can induce spatial synchronization in neuronal circuits defined by the morphological territory of the astrocyte [2][3][4]. In other words one can draw an analogy with the Hopfield network.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in thin dendritic branches of neurons and astrocytes, optical measurements perform better than electrode recordings, in terms of calcium activity (Schiller et al, 1995; Kampa et al, 2006), membrane potential transients (Zhou et al, 2008), and also for recording ion currents (Jaafari et al, 2014; Jaafari and Canepari, 2016; Ait Ouares et al, 2019). In summary, the places where electrodes cannot go, optical measurements are taking over (Popovic M. A. et al, 2015; Bindocci et al, 2017; Gordleeva et al, 2019).…”
mentioning
confidence: 99%